Learning Configurations and Teaching Knowledge - Sérgio Silva Filgueira; Sergio de Mello Arruda; Marinez Meneghello Passos (Universidade Federal do Rio Grande do Sul, 2019)
This paper presents the results of a study carried out with students from a public school in the state of Goiás. We involved the students in situations of research/experimentation, interviewed the teacher about his planning and analyzed the reports of his practice according to the Strands of Science Learning (SSL). It was evidenced that engaging in scientific reasoning prevailed in the teacher's planning and practice. Engaging in scientific practice, which presented a high intensity in planning, was reduced during teaching. During classes, learning of science knowledge was enhanced. Therefore the SSL help understand and characterize teaching practice and student learning in learning configurations based on the experimentation process.